Conceptualizing Israeli public diplomacy towards the United States of America on the Palestine-Israel conflict based on grounded theory / Noor Nirwandy Mat Noordin - Mat Noordin, Noor Nirwandy (Institute of Graduate Studies, UiTM, 2018)
Palestine-Israel conflict is an ongoing conflict that has yet to find any agreeable solution. The conflict has continuously been referred to as the conflict between two sides with unequal strength, as Israel is perceived to have advantages over the situation because of its military strengths and international supports particularly from a super power nation, the United States (US). Israel is perceived as using Public Diplomacy approaches towards the US on Palestine-Israel conflict. Israel uses Public Diplomacy to win US support on the conflict. However, little knowledge is available to understand on how Israel Public Diplomacy application towards the US is conducted on the Palestine-Israel conflict. Therefore, this research focuses on studying the underlying application of Israel Public Diplomacy towards the US on the Palestine-Israel conflict. Using the Grounded Theory approach, the objective of this research is to identify Israel Public Diplomacy approaches, to develop a theoretical understanding and to construct a substantive theory in conceptualizing Israel's Public Diplomacy strategy towards US on the Palestine-Israel conflict. Through Grounded Theory, the research inductively explores how Israel's Public Diplomacy conducts towards the US on the Palestine- Israel conflict. Nine respondents were interviewed in this research. The findings have identified religious approaches applied through core conceptualized context and strategic cooperation engagement applied through formal strategic cooperation to explain Israel's Public Diplomacy applications towards the US on the Palestine-Israel conflict…